ANALYSIS OF DIGITAL MARKETING COMMUNICATION MIX STRATEGIES FOR INDOMIE PRODUCTS: MULTICHANNEL INTEGRATION FOR OPTIMIZING BRAND ENGAGEMENT AND CONSUMER LOYALTY - Romy Di Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The development of digital technology encourages companies to adopt more integrated and multi-channel marketing communication strategies to maintain competitiveness amidst increasingly fierce market competition. This study aims to analyze the effectiveness of the digital marketing communication mix implemented by Indomie through the "Hype Abis" campaign in increasing consumer engagement, brand awareness, sales, and customer loyalty. This study uses a qualitative approach with a literature review method of various scientific sources relevant to digital marketing communications, B2C, B2B, and C2B strategies, and consumer behavior in the instant noodle industry. The results of the study indicate that Indomie's multi-channel digital marketing strategy, including social media integration, collaboration with influencers, creative content based on digital culture trends, and optimization of e-commerce platforms, has proven effective in creating a viral effect, increasing sales, and strengthening emotional connections with consumers. In addition, active consumer participation through user-generated content (C2B) contributes to increased customer loyalty. Evaluation of campaign performance through Key Performance Indicators (KPIs) is an important factor in ensuring the effectiveness of digital marketing communication strategies. This study recommends developing strategies through the use of innovative technology, data-driven approaches, strengthening digital loyalty programs, and expanding strategies to the B2B segment to support the sustainable growth of the Indomie brand.